Urban Rail Development in China : Issues and Options - World Bank (Washington, DC, 2014)
The Institute of Comprehensive Transport (NDRC) and the World Bank jointly carried out a study of urban rail development in China. The joint study team visited several selected cities that have developed or are developing urban rail systems, including Beijing, Chongqing, Wuhan, Changsha, Hangzhou, and Zhengzhou, and held discussions with relevant agencies at the central and local levels. This paper summarizes the key findings. It highlights the positive outlook for urban rail development in China and the strengths of China's circumstances and institutions in responding to that outlook. It also identifies the key areas where strengthening of institutions and processes of urban rail planning would enhance the contribution of urban railways to sustainable urban development and improve value for money from specific urban rail investments. It makes seven recommendations aimed at such strengthening. The study is intended to contribute both to urban rail policy and planning in China's cities and also to help the World Bank target its institutional support in this important sub-sector of China's transport system.